Epstein‐Barr viral loads do not predict post‐transplant lymphoproliferative disorder in pediatric lung transplant recipients: A multicenter prospective cohort study. (21st June 2017) - Parrish, Andrew; Fenchel, Matthew; Storch, Gregory A.; Buller, Richard; Mason, Sheila; Williams, Nikki; Ikle, David; Conrad, Carol; Faro, Albert; Goldfarb, Samuel; Hayes, Don; Melicoff‐Portillo, Ernestina; et al.
Abstract: Prediction of PTLD after pediatric lung transplant remains difficult. Use of EBV VL in WB has been poorly predictive, while measurement of VL in BAL fluid has been suggested to have enhanced utility. The NIH‐sponsored Clinical Trials in Organ Transplantation in Children (CTOTC‐03) prospectively obtained serial quantitative measurements of EBV PCR in both WB and BAL fluid after pediatric lung transplantation. Descriptive statistics, contingency analyses, and Kaplan‐Meier analyses evaluated possible association between EBV and PTLD. Of 61 patients, 34 (56%) had an EBV+PCR (at least once in WB or BAL). EBV donor (D)+patients more often had a positive PCR (D+/recipient (R)−: 13/18; D+/R+: 14/23) compared to EBV D‐ patients (6/17). Several D−/R− (5/12) patients developed EBV, but none developed PTLD. All four PTLD patients were D+/R− with EBV+PCR. Neither the time to first EBV+PCR nor the CT for PCR positivity in BAL or WB was statistically different between those with and without PTLD. Having an EBV‐seropositive donor was associated with increased risk of EBV+PCR in WB. EBV load in BAL was not predictive of PTLD.